Prolonged time interval from neoadjuvant immunotherapy combined with chemotherapy to surgery is related to unimproved pathological response and poor survival prognosis for esophageal squamous cell carcinoma - Guanzhi Ye; Gaojian Pan; Xiaolei Zhu; Hongming Liu; Ning Li; Guojun Geng; Jie Jiang (BMC Gastroenterology)
Abstract Background The optimal time interval from neoadjuvant immunotherapy combined with chemotherapy to surgery for esophageal squamous cell carcinoma remains unknown. This research aims to assess the impact of time interval on pathological response and survival prognosis. Methods Esophageal squamous cell carcinoma patients receiving neoadjuvant immunotherapy combined with chemotherapy followed by esophagectomy between January 2021 and March 2024 were included. The pathological response, survival outcomes, surgical outcomes, and postoperative complications were compared between the timely surgery group (time interval ≤ 6 weeks) and the delayed surgery group (time interval > 6 weeks). Results A total of 133 cases were included in this research. The pathological complete response (pCR) rates in timely surgery group and delayed surgery group were 23.4% and 12.8% (P = 0.167). There were no statistically significant differences between the two groups in terms of anastomotic fistula (P = 0.321), pulmonary infection (P = 0.427), chylothorax (P = 0.502), multiple organ dysfunction syndrome (P = 0.206), operation time (P = 0.359), blood loss (P = 0.093), number of resected lymph nodes (P = 0.091), hospital stay (P = 0.167), and R0 resection rate (P = 0.523). The 3-year overall survival (OS) rates were 77.5% in timely surgery group, and 63.5% in delayed surgery group (P = 0.046). The 3-year disease-free survival (DFS) rates were 59.1% and 38.4% in the two groups, respectively (P = 0.037). Additionally, multivariate Cox regression analyses indicated that the time interval from immunochemotherapy to surgery was independent prognostic factor for both OS (P = 0.049) and DFS (P = 0.025). Conclusions Prolonged time interval from neoadjuvant immunotherapy combined with chemotherapy to surgery did not improve pCR rate and was associated with worse OS and DFS in esophageal squamous cell carcinoma.